Tuning the affinity of aminoacyl-tRNA to elongation factor Tu for optimal decoding - Schrader, Jared M; Chapman, Stephen J; Uhlenbeck, Olke C (Proceedings of the National Academy of Sciences - PNAS, 2011)
To better understand why aminoacyl-tRNAs (aa-tRNAs) have evolved to bind bacterial elongation factor Tu (EF-Tu) with uniform affinities, mutant tRNAs with differing affinities for EF-Tu were assayed for decoding on Escherichia coli ribosomes. At saturating EF-Tu concentrations, weaker-binding aa-tRNAs decode their cognate codons similarly to wild-type tRNAs. However, tighter-binding aa-tRNAs show reduced rates of peptide bond formation due to slow release from EF-Tu•GDP. Thus, the affinities of aa-tRNAs for EF-Tu are constrained to be uniform by their need to bind tightly enough to form the ternary complex but weakly enough to release from EF-Tu during decoding. Consistent with available crystal structures, the identity of the esterified amino acid and three base pairs in the T stem of tRNA combine to define the affinity of each aa-tRNA for EF-Tu, both off and on the ribosome.